Bioluminescence: Fundamentals and Applications in Biotechnology - Volume 3 - Thouand, Gérald; Marks, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Lux and luc genes as reporter reactions : how to use them in molecular biology ? -- Measurement of bioluminescence intensity and spectrum: current physical techniques and principles -- Structure, Mechanism and Mutation of Bacterial Luciferase -- Detection of metals and organometallic compounds with microbial bioluminescent bioassays -- Bioluminescent microbial biosensors applied to on line detection of chemicals -- Let there be light! Bioluminescent imaging to study bacterial pathogenesis in live animals and plants -- Uses of the Photoprotein Aequorin in Biotechnology: Fundamental Properties and Genetic Engineering -- Whole-Cell Biosensors as Tools for the Detection of Quorum Sensing Molecules: Uses in Diagnostics and the Investigation of the Quorum Sensing Mechanism.
Keywords: Industrial microbiology; Biotechnology; Biochemistry; Industrial Microbiology; Chemical Bioengineering; Chemical Biology